IDENTIFICATION OF LEAF RUST RESISTANCE GENES IN SPECIES OF AEGILOPS L., SYNTHETIC FORMS, AND INTROGRESSION LINES OF COMMON WHEAT - E. R. Davoyan; R. O. Davoyan; I. V. Bebyakina; O. R. Davoyan; Yu. S. Zubanova; A. M. Kravchenko; A. N. Zinchenko (Вавиловский журнал генетики и селекции, 2014)
DNA samples of wild relatives, synthetic forms and introgression lines of common wheat (Triticum aestivum L.) have been genotyped with diagnostic molecular markers linked to known leaf rust resistance genes Lr9, Lr35 and Lr47. The Lr9 gene is present identified in Aegilops umbellulata, and Lr35 and Lr47, in Ae. speltoides. The synthetic forms Avrolata and Avrodes, with the substitution of the genomes of A е. umbellulata and Aе. speltoides, respectively, for the wheat D-genome, possess Lr9 and Lr35 genes. The genomes of the introgression lines developed using Aе. umbellulata lack Lr9. The Lr35 gene is present in one of the introgression lines derived from Avrodes. Some of the wild relatives and the introgression lines are suggested to have additional leaf rust resistance genes.